2020
DOI: 10.4018/ijcallt.2020010104
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Cultural Understanding with Virtual Reality

Abstract: In virtual reality, language learners can experience the foreign culture by exploring authentic and contextualized learning environments. To date, there is a lack of studies investigating the use of highly immersive virtual reality for cultural understanding as well as learners' attitudes toward its implementation in the language classroom. This study addresses this gap by exploring language learners' stereotypes and generalizations of the foreign culture experienced in highly immersive virtual reality, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 22 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…18 articles investigated AR and VR supported speaking, e.g., [26][27][28]. 10 studies examined AR and VR for writing, e.g., [29][30][31], and another 10 discussed AR and VR enhanced cultural learning, e.g., [32][33][34]. In addition, AR and VR tools were used to promote development of language skills and knowledge such as reading, e.g., [35,36], listening, e.g., [37,38], integral language learning, e.g., [39,40], Chinese character, e.g., [41,42]; grammar learning e.g., [43,44] and English alphabet [45,46].…”
Section: The Data Coding and Analysis Processesmentioning
confidence: 99%
“…18 articles investigated AR and VR supported speaking, e.g., [26][27][28]. 10 studies examined AR and VR for writing, e.g., [29][30][31], and another 10 discussed AR and VR enhanced cultural learning, e.g., [32][33][34]. In addition, AR and VR tools were used to promote development of language skills and knowledge such as reading, e.g., [35,36], listening, e.g., [37,38], integral language learning, e.g., [39,40], Chinese character, e.g., [41,42]; grammar learning e.g., [43,44] and English alphabet [45,46].…”
Section: The Data Coding and Analysis Processesmentioning
confidence: 99%
“…As has been documented in the literature (e.g. Berti et al, 2020;Kaplan-Rakowski & Gruber, 2019), the different levels of immersion are largely due to the equipment used to experience the VR. In low-immersion…”
Section: Introductionmentioning
confidence: 92%
“…More recently, Berti et al (2020) used three 360 degree VR videos recorded by one of them in the city of Bergamo, Italy, to investigate the influence of highly-immersive VR on Italian as an FL students' preconceived ideas of Italy and Italians. Findings from written reflections and focus group interviews showed that the 360 degree VR videos allowed students to reduce their use of stereotypes.…”
Section: Research On the Use Of Vr For Second Language Learning Involmentioning
confidence: 99%
See 2 more Smart Citations